Polyurethane plastic material and preparation method thereof
By introducing styrene-ethylene-butene-styrene block copolymer emulsion and nanoorganic bentonite into polyurethane plastic materials, the problem of insufficient aging resistance of traditional polyurethane materials is solved, and the material's moisture and heat aging resistance is significantly improved and The product has a longer service life.
Patent Information
- Application Number
- CN202411795121.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-02-14
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
During long-term use, polyurethane plastic materials used for insulation such as refrigerators and refrigerators have insufficient aging resistance, which affects the service life of the product.
The material is enhanced by introducing styrene-ethylene-butene-styrene block copolymer emulsion into the polyurethane foaming system and limiting its solid content and particle size, as well as the use of nanoorganic bentonite and ultrasonic dispersion techniques during the preparation process. Resistant to moisture and heat aging.
It effectively improves the aging resistance of polyurethane foam materials, avoids aging failure caused by stress concentration and humid and heat environment, and extends the service life of the product.
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of polymer plastic materials, and more specifically, relates to a polyurethane plastic material and a preparation method thereof. Background Art
[0002] Among polyurethane plastic materials, rigid polyurethane foam materials have good mechanical properties, especially lower thermal conductivity and better thermal insulation performance than ordinary thermal insulation materials, making them high-quality lightweight thermal insulation support materials widely used in refrigerators, freezers, and building panels. In the process of preparing rigid polyurethane foam, a certain amount of physical foaming agent is required, and the type and amount of physical foaming agent will greatly affect the various properties of rigid polyurethane foam.
[0003] During the use of household appliances such as refrigerators and freezers, the problem of overall performance aging and attenuation is difficult to avoid. Since rigid polyurethane foam is an extremely important thermal insulation support material, the study of the aging and attenuation of rigid polyurethane foam performance becomes very important. However, in the increasingly complex foaming system, new foaming systems are gradually emerging. In the preparation process of the product, how to achieve a balance between mechanical properties and aging resistance is one of the technical problems that technicians in this field need to face in the process of new product development. Summary of the invention
[0004] The technical problem to be solved by the present invention is that the polyurethane plastic material traditionally used for heat preservation in refrigerators and freezers is prone to insufficient aging resistance during long-term use, thereby affecting the service life of the product. Based on the above problem, the present invention provides a polyurethane plastic material and a preparation method thereof.
[0005] The purpose of the present invention is to provide a method for preparing a polyurethane plastic material.
[0006] Another object of the present invention is to provide a polyurethane plastic material.
[0007] The above-mentioned purpose of the present invention is achieved through the following technical solutions:
[0008] A method for preparing a polyurethane plastic material, the specific preparation steps comprising:
[0009] Mix component A and component B evenly to obtain a premix;
[0010] The premix is poured into a mold, heated and insulated for foaming, and then aged and demoulded to obtain a polyurethane plastic material;
[0011] Wherein, the mass ratio of the component A to the component B is 1:0.95-1.05;
[0012] The A component is a polyisocyanate;
[0013] The B component includes the following raw materials in parts by weight:
[0014] 80-90 parts of polyether polyol, 10-15 parts of styrene-ethylene-butylene-styrene block copolymer emulsion, 8-10 parts of triethylamine, 6-8 parts of foaming agent, 2-3 parts of foam stabilizer;
[0015] The solid content of the styrene-ethylene-butylene-styrene block copolymer emulsion is 20-25%;
[0016] The emulsion particles D50 of the styrene-ethylene-butylene-styrene block copolymer emulsion are 4-10 μm.
[0017] The above technical solution introduces styrene-ethylene-butylene-styrene block copolymer emulsion into the polyurethane foaming system, and limits the corresponding solid content of the emulsion and the D50 size of the emulsion particles; firstly, by adding a certain amount of styrene-ethylene-butylene-styrene block copolymer emulsion, it can be used as a part of the polyurethane rigid foam material after the polyurethane is cured, thereby improving the flexibility of the foam body and avoiding stress concentration during the curing process, thereby effectively reducing the weak positions that are aged and failed during subsequent use due to stress concentration; secondly, during use, under wet and hot aging conditions, moisture will gradually diffuse and penetrate into the interior of the polyurethane foam. With the absorption of water molecules, the styrene-ethylene-butylene-styrene block copolymer can gradually expand and block the diffusion path of the water molecules, thereby effectively avoiding further damage to the polyurethane foam by the wet and hot environment, thereby significantly improving the aging resistance of the product;
[0018] The reason for choosing a suitable solid content is that if the solid content is too low, the effect of the styrene-ethylene-butylene-styrene block copolymer emulsion on the polyurethane foam will be too weak, and if the solid content is too high, it will be difficult to disperse it evenly on the foam surface during the polyurethane foaming process. At the corresponding solid content, choosing a suitable particle size will also help it to disperse quickly and evenly on the surface of the foam liquid film, so that the overall moisture and heat aging resistance of the product is uniform and reliable.
[0019] Furthermore, the foaming agent is compounded by trans-1-chloro-3,3,3-trifluoropropylene and a low-boiling-point foaming agent in a mass ratio of 10:1-0.8;
[0020] Wherein, the low boiling point foaming agent is selected from any one of butane, difluoroethane and tetrafluoroethane.
[0021] By using a certain amount of low-boiling point foaming agent for compounding, a richer foam system can be constructed, so that the foam composition includes large bubbles and small bubbles, so that during the product undergoing wet heat aging, the smaller bubbles can play a certain stress dispersion role on the larger bubbles; in particular, during the water diffusion process, the volume change of the styrene-ethylene-butylene-styrene block copolymer is caused, and the small bubbles around the large bubbles have a shorter blocking path and can also play an effect of quickly and synergistically blocking the water molecule transfer path.
[0022] Furthermore, the foam stabilizer is selected from any one of polyoxyethylene polydimethylsiloxane, polyoxypropylene polydimethylsiloxane, fatty alcohol polyoxyethylene ether polydimethylsiloxane, and fatty alcohol polyoxypropylene ether polydimethylsiloxane.
[0023] Furthermore, the B component also includes 6-8% of the mass of the polyether polyol nanoorganic bentonite;
[0024] Furthermore, before stirring and mixing the component B with the component A, the component B is first subjected to ultrasonic dispersion at an ultrasonic frequency of 200-220 kHz for 40-60 minutes.
[0025] Furthermore, the nano-organic bentonite is monodisperse nano-organic bentonite, and the particle size distribution range of the monodisperse nano-organic bentonite is 80-100 nm.
[0026] The above technical solution further introduces nano-organic bentonite into the system, and in the process of preparing the product, a continuous ultrasonic treatment is performed at a frequency higher than 200kHz for more than 40 minutes. Under the cavitation effect of the ultrasonic wave, the interlayer spacing of the organic bentonite is widened, and even partial peeling between layers occurs. Therefore, after it is added to the foaming system, it can be evenly dispersed on the surface of the liquid film, and after the interlayer spacing is widened, the thermal resistance between the layers is also improved, so that the introduction of the organic bentonite will not reduce the thermal insulation performance of the polyurethane foam system; in addition, in the process of the styrene-ethylene-butylene-styrene block copolymer absorbing water molecules and expanding, the presence of the organic bentonite after the interlayer spacing is widened can also play a role in alleviating the expansion stress, and under the action of the expansion stress, it can also help block the diffusion path of water molecules.
[0027] Furthermore, the polyether polyol is selected from any one of polyoxypropylene glycol, polytetrahydrofuran diol, and tetrahydrofuran-oxypropylene copolymer glycol.
[0028] Furthermore, the polyisocyanate is selected from any one of toluene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate, and dicyclohexylmethane-4,4'-diisocyanate.
[0029] A polyurethane plastic material is prepared by the above preparation method. DETAILED DESCRIPTION
[0030] The present invention is further described below with reference to specific examples, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.
[0031] Unless otherwise specified, the reagents and materials used in the following examples are commercially available.
[0032] Example 1
[0033] Prepare the following raw materials by weight for preparing component B:
[0034] 80 parts of polyether polyol, 10 parts of styrene-ethylene-butylene-styrene block copolymer emulsion, 8 parts of triethylamine, 6 parts of foaming agent, 2 parts of foam stabilizer; and 6% of the mass of the polyether polyol nano-organic bentonite;
[0035] After mixing polyether polyol, styrene-ethylene-butylene-styrene block copolymer emulsion, triethylamine, foaming agent, foam stabilizer and nano-organic bentonite, ultrasonic dispersion was performed at an ultrasonic frequency of 200 kHz for 40 minutes to obtain component B;
[0036] The solid content of the styrene-ethylene-butylene-styrene block copolymer emulsion is 20%;
[0037] The emulsion particles D50 of the styrene-ethylene-butylene-styrene block copolymer emulsion is 4 μm;
[0038] The foaming agent is prepared by compounding trans-1-chloro-3,3,3-trifluoropropylene and a low-boiling-point foaming agent in a mass ratio of 10:1;
[0039] Wherein, the low boiling point blowing agent is selected from butane;
[0040] The foam stabilizer is selected from polyoxyethylene polydimethylsiloxane;
[0041] The nano-organic bentonite is a monodisperse nano-organic bentonite, and the particle size distribution range of the monodisperse nano-organic bentonite is 80-100 nm;
[0042] The polyether polyol is selected from polyoxypropylene glycol;
[0043] At a temperature of 20°C, component A and component B were stirred and mixed with a stirrer at a speed of 300 r / min for 3 minutes to obtain a premix;
[0044] The mold is preheated to 45°C, and then the premix is poured into the mold, and the mold is kept warm for foaming, and then aged at 20°C for 48 hours, and demolded to obtain a polyurethane plastic material;
[0045] Wherein, the mass ratio of the component A to the component B is 1:0.95;
[0046] The A component is a polyisocyanate;
[0047] The polyisocyanate is selected from toluene diisocyanate.
[0048] Example 2
[0049] Prepare the following raw materials by weight for preparing component B:
[0050] 90 parts of polyether polyol, 15 parts of styrene-ethylene-butylene-styrene block copolymer emulsion, 10 parts of triethylamine, 8 parts of foaming agent, 3 parts of foam stabilizer; and 8% of the mass of the polyether polyol nanoorganic bentonite;
[0051] After mixing polyether polyol, styrene-ethylene-butylene-styrene block copolymer emulsion, triethylamine, foaming agent, foam stabilizer and nano-organic bentonite, ultrasonic dispersion was performed at an ultrasonic frequency of 220 kHz for 60 minutes to obtain component B;
[0052] The solid content of the styrene-ethylene-butylene-styrene block copolymer emulsion is 25%;
[0053] The emulsion particles D50 of the styrene-ethylene-butylene-styrene block copolymer emulsion are 10 μm;
[0054] The foaming agent is prepared by compounding trans-1-chloro-3,3,3-trifluoropropylene and a low-boiling-point foaming agent in a mass ratio of 10:0.8;
[0055] Wherein, the low boiling point blowing agent is selected from difluoroethane;
[0056] The foam stabilizer is selected from polyoxypropylene polydimethylsiloxane;
[0057] The nano-organic bentonite is a monodisperse nano-organic bentonite, and the particle size distribution range of the monodisperse nano-organic bentonite is 80-100 nm;
[0058] The polyether polyol is selected from polytetrahydrofuran diol;
[0059] At a temperature of 25°C, component A and component B were stirred and mixed with a stirrer at a speed of 300 r / min for 5 minutes to obtain a premix;
[0060] The mold is preheated to 45°C, and then the premix is poured into the mold, and the mold is kept warm for foaming, and then aged at 25°C for 52 hours, and demolded to obtain a polyurethane plastic material;
[0061] Wherein, the mass ratio of the component A to the component B is 1:1.05;
[0062] The A component is a polyisocyanate;
[0063] The polyisocyanate is selected from diphenylmethane diisocyanate.
[0064] Example 3
[0065] Prepare the following raw materials by weight for preparing component B:
[0066] 85 parts of polyether polyol, 12 parts of styrene-ethylene-butylene-styrene block copolymer emulsion, 9 parts of triethylamine, 7 parts of foaming agent, 2.6 parts of foam stabilizer; and 7% of the mass of the polyether polyol nanoorganic bentonite;
[0067] After mixing polyether polyol, styrene-ethylene-butylene-styrene block copolymer emulsion, triethylamine, foaming agent, foam stabilizer and nano-organic bentonite, ultrasonic dispersion was performed at an ultrasonic frequency of 210 kHz for 50 minutes to obtain component B;
[0068] The solid content of the styrene-ethylene-butylene-styrene block copolymer emulsion is 22%;
[0069] The emulsion particles D50 of the styrene-ethylene-butylene-styrene block copolymer emulsion are 8 μm;
[0070] The foaming agent is prepared by compounding trans-1-chloro-3,3,3-trifluoropropylene and a low-boiling-point foaming agent in a mass ratio of 10:0.9;
[0071] Wherein, the low boiling point foaming agent is selected from tetrafluoroethane;
[0072] The foam stabilizer is selected from fatty alcohol polyoxyethylene ether polydimethylsiloxane;
[0073] The nano-organic bentonite is a monodisperse nano-organic bentonite, and the particle size distribution range of the monodisperse nano-organic bentonite is 80-100 nm;
[0074] The polyether polyol is selected from tetrahydrofuran-propylene oxide copolymer glycol;
[0075] At a temperature of 22°C, component A and component B were stirred and mixed with a stirrer at a speed of 300 r / min for 4 minutes to obtain a premix;
[0076] The mold is preheated to 45°C, and then the premix is poured into the mold, and the mold is kept warm for foaming, and then aged at 22°C for 50 hours, and demolded to obtain a polyurethane plastic material;
[0077] Wherein, the mass ratio of the component A to the component B is 1:1;
[0078] The A component is a polyisocyanate;
[0079] The polyisocyanate is selected from hexamethylene diisocyanate.
[0080] Example 4
[0081] The difference between this embodiment and embodiment 1 is that no nano-organic bentonite is added, and other conditions remain unchanged.
[0082] Example 5
[0083] The present embodiment is different from the embodiment 1 in that the particle size distribution range of the nano-organic bentonite is 10-100 nm; and the other conditions remain unchanged.
[0084] Example 6
[0085] The present embodiment is different from the embodiment 1 in that the solid content of the styrene-ethylene-butylene-styrene block copolymer emulsion is 30%, and the other conditions remain unchanged.
[0086] Example 7
[0087] The present embodiment is different from the embodiment 1 in that the D50 of the styrene-ethylene-butylene-styrene block copolymer emulsion is 15 μm, and the other conditions remain unchanged.
[0088] Comparative Example 1
[0089] The difference between this comparative example and Example 1 is that no styrene-ethylene-butylene-styrene block copolymer emulsion is added, and other conditions remain unchanged.
[0090] The performance tests were performed on the products obtained in the examples and comparative examples. The specific test methods and test results are as follows:
[0091] Refer to GB / T 8813-2008 "Determination of compression properties of rigid foam plastics" to test the compression strength of the product;
[0092] The specific test method is as follows:
[0093] The test was conducted using UTM-1422 universal material testing machine;
[0094] The products of the embodiments and comparative examples were made into samples with a specification of 100mm×100mm×50mm. Two samples were made for each embodiment or comparative example, one of which was directly tested with reference to the above standard, and the other sample was transferred to an aging test box, and the temperature was 45°C and the relative humidity was 80%. After continuous simulated aging for 28 days, it was taken out, dried to remove moisture, and then tested with reference to the above standard to obtain the compressive strength before aging and the compressive strength after aging, respectively. Please refer to Table 1 for details;
[0095] Table 1: Product performance test results
[0096] Compression strength before aging / MPa Compression strength after aging / MPa Example 1 4.95 4.93 Example 2 5.12 5.10 Example 3 5.08 5.05 Example 4 4.55 4.45 Example 5 4.72 4.65 Example 6 4.78 4.70 Example 7 4.81 4.73 Comparative Example 1 4.73 4.50
[0097] It can be seen from the test results in Table 1 that the product obtained by the present invention can still maintain relatively high mechanical properties after the continuous aging test.
[0098] The above embodiments are preferred implementation modes of the present invention, but the implementation modes of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications that do not deviate from the spirit and principles of the present invention should be equivalent replacement methods and are included in the protection scope of the present invention.
Claims
1. A method for preparing a polyurethane plastic material, characterized in that: The specific preparation steps include: Mix component A and component B evenly to obtain a premix; The premix is poured into a mold, heated and insulated for foaming, and then aged and demoulded to obtain a polyurethane plastic material; Wherein, the mass ratio of the component A to the component B is 1:0.95-1.05; The A component is a polyisocyanate; The B component includes the following raw materials in parts by weight: 80-90 parts of polyether polyol, 10-15 parts of styrene-ethylene-butylene-styrene block copolymer emulsion, 8-10 parts of triethylamine, 6-8 parts of foaming agent, 2-3 parts of foam stabilizer; The solid content of the styrene-ethylene-butylene-styrene block copolymer emulsion is 20-25%; The emulsion particles D50 of the styrene-ethylene-butylene-styrene block copolymer emulsion are 4-10 μm.
2. The method for preparing a polyurethane plastic material according to claim 1, characterized in that: The foaming agent is prepared by compounding trans-1-chloro-3,3,3-trifluoropropylene and a low boiling point foaming agent in a mass ratio of 10:1-0.8; Wherein, the low boiling point foaming agent is selected from any one of butane, difluoroethane and tetrafluoroethane.
3. The method for preparing a polyurethane plastic material according to claim 1, characterized in that: The foam stabilizer is selected from any one of polyoxyethylene polydimethylsiloxane, polyoxypropylene polydimethylsiloxane, fatty alcohol polyoxyethylene ether polydimethylsiloxane and fatty alcohol polyoxypropylene ether polydimethylsiloxane.
4. The method for preparing a polyurethane plastic material according to claim 1, characterized in that: The B component also includes 6-8% of the mass of the polyether polyol nanoorganic bentonite; Furthermore, before stirring and mixing the component B with the component A, the component B is first subjected to ultrasonic dispersion at an ultrasonic frequency of 200-220 kHz for 40-60 minutes.
5. The method for preparing a polyurethane plastic material according to claim 4, characterized in that: The nano-organic bentonite is monodisperse nano-organic bentonite, and the particle size distribution range of the monodisperse nano-organic bentonite is 80-100 nm.
6. The method for preparing a polyurethane plastic material according to claim 1, characterized in that: The polyether polyol is selected from any one of polyoxypropylene glycol, polytetrahydrofuran glycol, and tetrahydrofuran-oxypropylene copolymer glycol.
7. The method for preparing a polyurethane plastic material according to claim 1, characterized in that: The polyisocyanate is selected from any one of toluene diisocyanate, diphenylmethane diisocyanate, hexamethylene diisocyanate, isophorone diisocyanate and dicyclohexylmethane-4,4'-diisocyanate.
8. A polyurethane plastic material, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 7.
Citation Information
Patent Citations
Hard polyurethane foam
CN105601978A
Hot-melt pressure-sensitive adhesive and preparation technology thereof
CN105694803A
Rigid polyurethane foam formula and preparation method thereof
CN110628073A
Hyper-elastic 3D printing nano cellulose composite material and preparation method thereof
CN112920538A
Polyurethane foam material, preparation method thereof, refrigerator and freezer
CN117940474A